Proyecto de factibilidad para la creación de la empresa que brinde un servicio de calidad y eficiencia en la manipulación de cargue y descargue de mercancías en la sociedad portuaria regional de Buenaventura. “Hombre Seguro” (2011)
The business plan "SAFE MAN" is a proposal that emerged from the two authors of the project which have work experience in the field of port work, and through their experiences through detailed observation on the problem processes of the cargo handling and view the business opportunity that means available to a port services company that offers the same service with higher quality. After establishing the rationale for the feasibility study and assessment of other elements such as the theoretical and conceptual, packing and unpacking, which would be defined methodology that produced the following data: descriptive, population and sample consisted of laborers, business owners of goods, port operators and port company. Once the proposal and defined the scope of the feasibility study developed the following phases: Market research: It identified the customers, competitors, channels, pricing, service offerings of the company "assured man" which is based on a percentage of import and export containers that pass inspection DIAN The ICA and anti-narcotics police, the strategies for positioning the service and marketing channels. Technical study: it was identified values, quantities, requirements, space and strategic location of the office and the elements in the area of operations, cargo handling. Administrative and legal study: The Company with its name, organization, fees, profiles, training and legal requirements regarding wages and taxation regime. Financial analysis: in the latter than the feasibility study were projected sales, costs, expenses, investments and established financial indicators showed the feasibility of the investment plan "SAFE MAN."